2007
DOI: 10.1653/0015-4040(2007)90[115:bocoko]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast of Champions or Kiss of Death? Survival and Sexual Performance of Protein-Fed, Sterile Mediterranean Fruit Flies (Diptera: Tephritidae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
115
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(124 citation statements)
references
References 29 publications
8
115
0
1
Order By: Relevance
“…The research was carried out under the CRP built on the aforementioned studies to understand Yuval et al 2007;Faria et al 2008;Weldon et al 2008;Pereira et al 2009Pereira et al , 2010aPereira et al ,b, 2013Haq et al 2010aHaq et al ,b, 2013Quilici et al 2013;Liedo et al 2013) Addition of protein to the pre-release diet significantly improved male weight and body protein content for A.…”
Section: Semiochemical Supplementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research was carried out under the CRP built on the aforementioned studies to understand Yuval et al 2007;Faria et al 2008;Weldon et al 2008;Pereira et al 2009Pereira et al , 2010aPereira et al ,b, 2013Haq et al 2010aHaq et al ,b, 2013Quilici et al 2013;Liedo et al 2013) Addition of protein to the pre-release diet significantly improved male weight and body protein content for A.…”
Section: Semiochemical Supplementsmentioning
confidence: 99%
“…The ratio of protein to carbohydrates in dry diets provisioned early in adult life contributed to male sexual performance and affected survival in a dose-dependent manner in A. fraterculus, A. ludens, A. obliqua and B. tryoni (Prabhu et al 2008;Gó mez et al 2013;Liedo et al 2013;Segura et al 2013; (Yuval et al 2007;Gavriel et al 2010;Taylor et al 2013) In the laboratory, protein-fed males lived significantly longer than sugar-fed males of B. cucurbitae and B. tryoni (Haq et al 2010b;Taylor et al 2013). The same was found in A. ludens and A. obliqua when the sugar/yeast ratio was 9:1 or 24:1, but not with the 3:1 ratio ) Inhibition of remating Feeding on a nitrogen-rich food significantly improved the ability of sterile males to inhibit female remating in A. fraterculus, B. tryoni and C. capitata (Harmer et al 2006;Radhakrishnan and Taylor 2007;Gavriel et al 2009;Segura et al 2013 The contribution of microorganisms to fitness of non-sterile Bactrocera oleae and C. capitata was established Ben-Yosef et al 2008aYuval et al 2013) Manipulating the microflora of sterile males suggests that probiotic supplements could improve male sexual performance in C. capitata (Niyazi et al 2004;Behar et al 2005Behar et al , 2008aBen-Ami et al 2010) these phenomena, to extend them to other species, and to transfer and validate them under large-scale conditions of action SIT programmes.…”
Section: Semiochemical Supplementsmentioning
confidence: 99%
“…El tiempo requerido varia entre especies, para C. capitata se reportan de 4 a 7 días, para A. ludens de 5 a 7 días y para A. obliqua 5 días (SAGARPA 1999;Tirado y Gómez-Escobar 2005). Si bien este tiempo puede ser utilizado para brindar a los machos condiciones que favorezcan su competitividad en el campo como son la exposición a volátiles que les confieren mayor competitividad sexual ) o una dieta con proteínas (Yuval et al 2007), es cierto que periodos largos pueden ser contraproducentes ya que se necesita espacio para mantener a las moscas y se incrementa la mortalidad por lo que se intenta reducir dichos tiempos mediante el uso de aceleradores del proceso de maduración sexual como es el metropeno, análogo de la hormona juvenil (Faria et al 2008). Este estudio sostiene la idea de que el tiempo de permanencia de los insectos bajo estas condiciones no afecta su comportamiento sexual y es probable que cualquier efecto se origine del manejo durante el empacado y liberado de los insectos.…”
Section: Discussionunclassified
“…Studies involving exposure to volatile compounds, aromatherapy with ginger oil (Morelli et al, 2010), dietary supplements (Yuval et al, 2007), and/or dietary modifications during early adult life Shelly, 2001), have been tested in attempts to improve the sexual competitiveness of mass-reared males under field conditions. In experiments with wild flies, Arita and Kaneshiro (1988) reported that C. capitata males that emerged from coffee berries copulated more frequently than males emerging from Jerusalem cherries (Solanum pseudocapsicum L.) -even though the latter insects were larger.…”
Section: Introductionmentioning
confidence: 99%